2016
DOI: 10.1002/hed.24403
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of MAGE and NY-ESO-1 cancer-testis antigens in adenoid cystic carcinoma of the head and neck

Abstract: Background Adenoid cystic carcinoma of the head and neck (ACC) is a rare but highly malignant tumor. Cancer testis antigens (CTA) represent an immunogenic family of cancer-specific proteins and thus represent an attractive target for immunotherapy. Methods Eighty-four cases of ACC were identified, the CTAs pan-MAGE (M3H67) and NY-ESO-1 (E978) were detected immunohistochemically and correlated with clinical data. Results Expression of NY-ESO-1 was found in 48/84 (57.1%) and of pan-MAGE in 28/84 (31.2%). Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
(104 reference statements)
1
11
3
Order By: Relevance
“…Veit et al . recently reported that immunohistochemistry showed the expression of pan‐MAGE and NY‐ESO‐1 in 31.2% and 57.1% of AdCC cases, respectively.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Veit et al . recently reported that immunohistochemistry showed the expression of pan‐MAGE and NY‐ESO‐1 in 31.2% and 57.1% of AdCC cases, respectively.…”
Section: Discussioncontrasting
confidence: 91%
“…To define immunohistochemical positivity, they considered both positive tumour cell ratios and signal intensities. Finally, they included many advanced AdCC cases, and more than half of the analysed AdCC cases had T3/4 tumours . In contrast, we used a commercially available anti‐MAGE‐A antibody (6C1) that recognizes MAGE‐A1, MAGE‐A2, MAGE‐A3, MAGE‐A4, MAGE‐A6, MAGE‐A10, and MAGE‐A12.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations